The Extent, Characteristics and Impacts of FDI and Multinational Firm Activities - A Firm Level Analysis - Martin Falk; Yvonne Wolfmayr (FIW - Research Centre International Economics, 2010)
The study examines the impact of Austrian outward foreign direct investments (FDI) on home based parent company employment. The analysis is based on the AMADEUS firm-level database and an improved methodology by applying matching methods and the difference in difference estimator. In this way we are able to overcome the major shortcomings of earlier studies on the home market effects of Austrian outward FDI, which included data on foreign direct investors only leading to biased estimates and preventing the deduction of causal relationships. Overall the results indicate that investing abroad strengthens the employment performance in the home country. This is also true for Austrian foreign direct investments in Eastern European locations. We also analyse the major factors determining the firms' decision to invest abroad as well as decisions on the degree of multinationality, which we measure by the number of foreign affiliates owned. Firm size, firm age, the capital intensity and the number of shareholders are significant determinants for the number of subsidiaries. The analysis also corroborates theoretical results establishing the fact that foreign direct investment activities are driven by firm specific advantages and a superior productivity performance in the pre-investment period. Thus, firms that start foreign activities are ex-ante different from non-investing purely domestic firms.
Keywords: F23; F21; J21; C35; 330; multinational enterprises; employment; propensity score matching